1999
DOI: 10.1007/bf03355404
|View full text |Cite
|
Sign up to set email alerts
|

On the failure criteria for unidirectional carbon fibre composite materials under compression

Abstract: In studying shear stresses that develop in the matrix as a consequence of microbuclding of fibres in a unidimensional composite it has been shown that the fibre failure criterion based on the tensile stresses on its convex side is not realistic because it gives shear strains in the su rrounding matrix which are beyond the ultimate shear strains measured experimentally. In fact, it is shown that fibres fail under local compression on their concave side before failing in local tension, and that such a compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…with perfectly bonded layers), , must be larger than the critical load, , for a material with the same internal structure containing cleavage-type delaminations, i.e. which in terms of strains means Hence, from Equations (7) and (10) and from Equation (8) and (11) The above-mentioned bounds were considered earlier for other material properties by Guz (25,26) , and also used later by Guz and Soutis (39) and Soutis and Guz (21) , where the investigation was restricted by the case of small deformations only, and by Guz and Herrmann (44) for incompressible hyperelastic materials.…”
Section: The Bounds For Critical Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…with perfectly bonded layers), , must be larger than the critical load, , for a material with the same internal structure containing cleavage-type delaminations, i.e. which in terms of strains means Hence, from Equations (7) and (10) and from Equation (8) and (11) The above-mentioned bounds were considered earlier for other material properties by Guz (25,26) , and also used later by Guz and Soutis (39) and Soutis and Guz (21) , where the investigation was restricted by the case of small deformations only, and by Guz and Herrmann (44) for incompressible hyperelastic materials.…”
Section: The Bounds For Critical Loadsmentioning
confidence: 99%
“…They could be due to the presence of holes, cut-outs and cracks, or generated by impact. Previous experimental studies (3)(4)(5)(6)(7) have revealed that a possible mechanism of failure initiation is fibre or layer microinstability (microbuckling) that may usually occur in regions where high stress gradients exist, for instance, near the edge of a hole or free edges (8)(9) .…”
Section: Introduction 11 Classification Of Different Approaches In Mmentioning
confidence: 99%
“…As a result of applying eqns (24), the "long-wave" approximation can be obtained. The term "long-wave" refers to the half-wavelength of the modes of stability loss along the OX i axisl i from eqns (14) (see figs [5][6][7][8]. Indeed, if α r → 0 and α m → 0 then l i → ∞.…”
Section: Asymptotic Analysis 31 the Long-wave Approximations (Transimentioning
confidence: 99%
“…They could be due to the presence of holes, cut-outs and cracks, or generated by impact. Previous experimental studies [1][2][3][4][5][6] have revealed that a possible mechanism of failure initiation is fiber or layer microinstability (microbuckling) that may usually occur in regions where high stress gradients exist, for instance, on the edge of a hole or near free edges [7,8]. A better understanding of the compression failure mechanisms, specific only to heterogeneous materials, is therefore crucial to the development of improved composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Microbuckling phenomena were first mentioned in [1] as a longitudinal short-wave bending, similar to the case of a beam on an elastic foundation [2], and modelled in [3]. Since that time further experimental observations have been reported and a variety of models have been proposed ( [4][5][6][7][8][9][10][11][12][13][14][15] and many others). The majority of existing nowadays models use simplified approaches, including 1-D and 2-D ones as well as those based on smearing the internal structure of the composite (the model of a continual medium).…”
Section: Introductionmentioning
confidence: 99%